Israel’s defence ethos: military service as a turning point - Itsik, Roen (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
Jewish culture deals a lot with survival stories – most of them became myths, especially since the establishment of the state of Israel. The Jewish ‘survival ethos’ is assimilated in Israel mostly by customs, traditions, and education. Above all, it has been claimed that military service in the Israel Defence Forces (IDF) is the most significant institution that empowers the survival ethos. As a result, it is assumed that those who serve in the IDF are characterized by hatred towards Arabs, and by being extreme nationalists. This claim is examined in the current article, which analyses the level of the sense of security threat among Israelis during the last decade, draws on data on military service and levels of trust in Israeli government institutions, and reveals an essential finding: Israeli’s survival ethos is being eroded among IDF soldiers. This finding, followed by the fact that the leaders of the liberal party in the Israeli parliament are former military generals, indicates that military service in Israel does not empower extreme nationalism; on the contrary, service in the IDF has become a moderating social mechanism.